Polymorphism and CDC25A Gene Expression in Pancreatic Cancer - Başar Aksoy; Erdal Uysal; Sacit Çoban; Serdar Öztuzcu (Sakarya Tıp Dergisi, 2016)
Background and Aim: The aim of this study is to determine the relationship between CDC25A gene polymorphism and pancreatic cancer via determiningCDC25A gene expression and polymorphisms of tumor tissues of pancreatic cancer cases. Additionally, it is aimed to prove thepossible relationship between cancer development and the gene expression level with determining CDC25A gene expressionlevels in tumor tissue and normal tissue.Materials and Methods: 118 patients (patients with pancreatic cancer who received surgery (n=28) and patients with pancreatic cancer who are in followup (n=90) and 83 healthy volunteers not having any known chronic disease and first degree relatives having cancer were includedin this study as a control group.Results: Ser88Phee polymorphisms in CDC25A gene of pancreatic cancer and control groups were compared according to C/C, C/T, T/Tgenotype frequencies and allele frequencies of C and T and no statistically significant difference was detected between twogroups (p gt;0.05). RS3731485 polymorphisms in CDC25A gene of pancreatic cancer and control groups were compared withrespect to C/C, C/G, G/G genotype frequencies and allele frequencies of C and G and there was no significant difference betweenthem statistically (p gt;0.05). There were no differences in CDC25A gene expression between control group and pancreatic cancergroup (p gt;0.05).Conclusion: In the light of the data obtained, any significant relationship at the CDC25A gene polymorphism and expression in pancreaticcancer was not detected. All in all, pancreatic cancer is a disease with high mortality and the place of genetics in the etiology ofcancer is indisputable. Therefore, we think the polymorphism and expression studies should be continued..